Whole genome sequencing of recombinant viruses obtained from co-infection and superinfection of Vero cells with modified vaccinia virus ankara vectored influenza vaccine and a naturally occurring cowpox virus - Diaz-Cánova, Diana; Moens, Ugo; Brinkmann, Annika; Nitsche, Andreas; Okeke, Malachy Ifeanyi (Frontiers in Immunology, 2024)
Modified vaccinia virus Ankara (MVA) has been widely tested in clinical trials as recombinant vector vaccine against infectious diseases and cancers in humans and animals. However, one biosafety concern about the use of MVA vectored vaccine is the potential for MVA to recombine with naturally occurring orthopoxviruses in cells and hosts in which it multiplies poorly and, therefore, producing viruses with mosaic genomes with altered genetic and phenotypic properties. We previously conducted co-infection and superinfection experiments with MVA vectored influenza vaccine (MVA-HANP) and a feline Cowpox virus (CPXV-No-F1) in Vero cells (that were semi-permissive to MVA infection) and showed that recombination occurred in both co-infected and superinfected cells. In this study, we selected the putative recombinant viruses and performed genomic characterization of these viruses. Some putative recombinant viruses displayed plaque morphology distinct of that of the parental viruses. Our analysis demonstrated that they had mosaic genomes of different lengths. The recombinant viruses, with a genome more similar to MVA-HANP (>50%), rescued deleted and/or fragmented genes in MVA and gained new host ranges genes. Our analysis also revealed that some MVA-HANP contained a partially deleted transgene expression cassette and one recombinant virus contained part of the transgene expression cassette similar to that incomplete MVA-HANP. The recombination in co-infected and superinfected Vero cells resulted in recombinant viruses with unpredictable biological and genetic properties as well as recovery of delete/fragmented genes in MVA and transfer of the transgene into replication competent CPXV. These results are relevant to hazard characterization and risk assessment of MVA vectored biologicals.